PREVALENCE OF INTERNET ADDICTION BY CIAS SCALE AND ASSOCIATED FACTORS AMONG STUDENTS AT THE BRANCH CAMPUS OF HANOI MEDICAL UNIVERSITY IN 2025 (Vietnam Journal of Community Medicine, 2026)
Objective: Describe the current state of internet addiction using the CIAS scale and investigate the factors related to internet addiction among students of the Branch Campus Hanoi Medical University in 2025.Methods: A cross-sectional descriptive study on 415 students from the first to the sixth year at the Branch Campus Hanoi Medical University in 2025, from 12/2024 to 6/2025. Data were collected by guiding participants to complete a structured self-administered questionnaire. Binary logistic regression analysis was employed to examine the association between psychological distress and the risk of internet addiction.Results: 40.2% of students meet the diagnostic criteria for internet addiction according to the CIAS assessment scale. The statistically significant factors related to internet addiction are: economic difficulties, a history of substance abuse, hours spent on the internet, the purpose of internet use, and psychological distress.Conclusion: A large proportion of students were at risk of or met the diagnostic criteria for internet addiction. According to an analysis of related factors, excessive internet use may be associated with a higher risk of addiction and increased levels of psychological stress among students. As a result, support programs should be established to increase students’ awareness of the negative consequences of internet addiction.
Keywords: Internet addiction, psychological distress, medical students.